Sarcoptic mange of camel in upper Egypt: Prevalence, risk assessment, and control measures - Kotb, Saber; Abdel-Rady, Ahmed (Journal of Advanced Veterinary and Animal Research, 2015)
This study was designed to reveal out the prevalence of Sarcoptic mite infestation and the risk factors associated with occurrence of mange in one-humped camels (Camulus dromedarius) at smallholder farms in Upper Egypt, and to develop an applicable therapeutical protocol for the Sarcoptic mange infested camels. A total of 660 one-humped camels were randomly selected from different villages of Assiut, Upper Egypt. The animals were undergone clinical and parasitological examinations. Skin scrapings revealed that Sarcoptes scabiei var. cameli mite was present in 6.06% (n=40/660) camels of the area. Statistical analysis of some ecological parameters showed that there was significant relationship (P<0.05) between mite infestation in camels and season, housing management, and use of acaricides. On the other hand, age and sex did not significantly affect the prevalence of the disease. Topical application of moxidectin at 0.5 mg/kg bwt or subcutaneous administration of doramectin at 200 ?g/kg bwt, along with treatment of animal environment was found to be the best protocol for the eradication and prevention of Sarcoptic mange in camel. The findings of this study indicate that Sarcoptes scabiei var cameli is the preeminent agent of mange infestation in one-humped camel in Upper Egypt. Use of acaricides for the treatment of affected camels, along with spraying the animal environment by insecticides is a effective protocol not only for controlling mange in camels but also for prevention of re-infestation from the animal environment. http://dx.doi.org/10.5455/javar.2015.b109